Sosialisasi Pencegahan Money Politik Dalam Menghadapi Pemilihan Kepala Daerah Tahun 2024 Kalimantan Selatan - Khairullah Anshari; Rizky Subhan; Junaidy Junaidy; Muhammad Halim; Ahmad Fitry (Lembaga Pengembangan Kinerja Dosen, 2024)
Community service activities with a focus on preventing the practice of money politics among South Kelayan community leaders. Money politics often undermines the integrity of elections and democracy, especially at the local level. In this context, we carry out a series of educational and outreach activities for community leaders to increase their understanding of the negative impacts of money politics and strategies for preventing it. The approach used involves seminars and discussions involving community leaders, youth and political party cadres. The results of this program show increased knowledge and commitment of community leaders in rejecting money politics and playing an active role in promoting clean and fair elections. During program implementation and provide recommendations for more effective money politics prevention efforts in the future. It is hoped that this experience can become a model for other regions facing similar problems, as well as contribute to strengthening local democracy and the integrity of general elections in Indonesia.